Peci and Sarung: Madurese Muslim Identity in Kamal, East Java - Muhajirin, Muhajirin; Muhammad, Afif; Rahman, Mohammad Taufiq (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
This study explores how peci (traditional cap) and sarong are represented as cultural-religious symbols that shape the collective identity of the Muslim Madurese community in Kamal District, Bangkalan, East Java. Using a descriptive qualitative approach and Stuart Hall’s theory of representation, the research was conducted through participatory observation, in-depth interviews, and documentation. The study employed an emic perspective by immersing the researcher in the everyday life of the Telang Dalem community. Findings reveal that peci and sarong are more than religious attire; they are symbols of identity transmitted across generations through family traditions, reinforced by the exemplary conduct of local kiai (Islamic scholars), and embedded in social-religious practices. These symbols serve as expressions of lived piety and loyalty to the moral authority of kiai, while also negotiating between inherited tradition and modern influences. The study concludes that such cultural symbols play a strategic role in preserving local religious identity. Theoretically, it contributes to the anthropology of Islam and identity studies; practically, it offers a model of contextualized religiosity that remains resilient amid social transformation.